Durà, Antoni; Camonita, Francesco; Berzi, Matteo i Noferini, Andrea (2018). Euroregions, excellence and innovation across EU borders: A Catalogue of good practices - Vicente i Rufí, Joan (Documents d'Anàlisi Geogràfica, 2020)
Durà, Antoni; Camonita, Francesco; Berzi, Matteo i Noferini, Andrea (2018) Euroregions, excellence and innovation across EU borders: A Catalogue of good practices Barcelona: UAB. Departament de Geografia, 254 p. ISBN ebook (PDF): 978-84-947903-9-3 ISBN paper 978-84-947903-8-6